Metformin inhibits OCT3-mediated serotonin transport in the placenta - Vachalova, Veronika; Kumnova, Fiona; Synova, Tetiana; Anandam, Kasin Yadunandam; Abad, Cilia; Karahoda, Rona; Staud, Frantisek (Biomedicine & pharmacotherapy, 2024)
Proper fetal development requires tight regulation of serotonin concentrations within the fetoplacental unit. This homeostasis is partly maintained by the placental transporter OCT3/SLC22A3, which takes up serotonin from the fetal circulation. Metformin, an antidiabetic drug commonly used to treat gestational diabetes mellitus, was shown to inhibit OCT3. We, therefore, hypothesized that its use during pregnancy could disrupt placental serotonin homeostasis. This hypothesis was tested using three experimental model systems: primary trophoblast cells isolated from the human term placenta, fresh villous human term placenta fragments, and rat term placenta perfusions. Inhibition of serotonin transport by metformin at three concentrations (1 μM, 10 μM, and 100 μM) was assessed in all three models. The OCT3 inhibitor decynium-22 (100 μM) and paroxetine (100 μM), a dual inhibitor of SERT and OCT3, were used as controls. In primary trophoblasts, paroxetine exhibited the strongest inhibition of serotonin uptake, followed by decynium-22. Metformin showed a concentration-dependent effect, reducing serotonin uptake by up to 57 % at the highest concentration. Its inhibitory effect was less pronounced in fresh villous fragments but remained statistically significant at all concentrations. In the perfused rat placenta, metformin demonstrated a concentration-dependent effect, reducing placental serotonin uptake by 44 % at the highest concentration tested. Our findings across all experimental models show inhibition of placental OCT3 by metformin, resulting in reduced serotonin uptake by the trophoblast. This sheds light on mechanisms that may underpin metformin-mediated effects on fetal development.
Keywords: Trophoblasts; Rats, Wistar; Organic Cation Transport Proteins; proteiny přenášející organické kationty; serotonin; oktamerní transkripční faktor 3; Pregnancy; pregnancy; OCT3; těhotenství; Placenta; trofoblasty; potkani Wistar; krysa rodu Rattus; kultivované buňky; biologický transport; placenta; metformin; hypoglykemika; Animals; lidé; ženské pohlaví; Humans; zvířata; gestational diabetes mellitus; Rats; Metformin; Hypoglycemic Agents; Cells, Cultured; Octamer Transcription Factor-3; Female; Serotonin; Biological Transport